2019
DOI: 10.1039/c9ra07735a
|View full text |Cite
|
Sign up to set email alerts
|

Generation of hydrogen sulfide during the thermal enhanced oil recovery process under superheated steam conditions

Abstract: During the thermal enhanced oil recovery process, the hazardous hydrogen sulfide (H2S) gas among the produced gases increases with superheated degree of vapor, which causes significant difficulty in the exploration and development of petroleum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The thermodynamic equilibrium calculations of water and product gases are calculated based on a version of the Peng–Robinson equation of state using specific terms for water: where P is the pressure, T the temperature, v f the molar volume, R the gas constant, a and b are interaction parameters among the different mixture compounds, and k ij is a binary interaction coefficient. Figure depicts the experimental H 2 S yield and calculated water vapor fraction as functions of the confining pressure of aquathermolysis. Experimental results indicate that the increase in confining pressure reduces the production of CO 2 and H 2 S. This trend was observed during aquathermolysis experiments of organosulfur compounds and heavy crude oil. , On the other hand, the results of the thermodynamic modeling indicate that at fluid pressures from 4 to 12 MPa, the gas phase was mainly composed of H 2 O (water vapor) and N 2 , at more than 90 mol %. While the H 2 O content in the gas phase decreased from 98 to 39 mol % with the increasing pressure.…”
Section: Effect Of Experimental Conditionsmentioning
confidence: 77%
See 3 more Smart Citations
“…The thermodynamic equilibrium calculations of water and product gases are calculated based on a version of the Peng–Robinson equation of state using specific terms for water: where P is the pressure, T the temperature, v f the molar volume, R the gas constant, a and b are interaction parameters among the different mixture compounds, and k ij is a binary interaction coefficient. Figure depicts the experimental H 2 S yield and calculated water vapor fraction as functions of the confining pressure of aquathermolysis. Experimental results indicate that the increase in confining pressure reduces the production of CO 2 and H 2 S. This trend was observed during aquathermolysis experiments of organosulfur compounds and heavy crude oil. , On the other hand, the results of the thermodynamic modeling indicate that at fluid pressures from 4 to 12 MPa, the gas phase was mainly composed of H 2 O (water vapor) and N 2 , at more than 90 mol %. While the H 2 O content in the gas phase decreased from 98 to 39 mol % with the increasing pressure.…”
Section: Effect Of Experimental Conditionsmentioning
confidence: 77%
“…It is important to emphasize that the different types of reactors do not directly influence the reaction kinetics as long as the same operating conditions are maintained (temperature, water/oil ratio, catalyst/reactant ratio, etc.). Experiments carried out with different reactor volumes showed that the degree of superheated steam (which is a function of the reactor volume) directly affects the yield of the aquathermolysis reactions since H 2 S production and heavy fraction conversion increased with an increase in the superheat degree under similar reaction temperature …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…with saturated steam, the higher enthalpy of superheated steam leads to more intense aquathermolysis reactions. [20] However, there are few researches on the steam chamber's growth characteristics of SSE-SAGD, which considers the influence of aquathermolysis reactions.…”
Section: Introductionmentioning
confidence: 99%